Analysis of hospitalizations of individuals aged 20 to 59 years for migraines and other headache syndromes in the southeastern region of Brazil from 2019 to 2023. - Boreggio, Hugo Berdejo; Schuch, Karolina Lemos; Caetano, Maria Clara Calixto; Stetter, Letícia Loreta Roque; Oliveira , Lorena Pedro de; Brandão , Brenda Lopes; Mota, Nicolas França; Silva, Celijane Almeida; Silva , Júlia Esteca da (Headache Medicine, 2024)
Introduction: Migraines and headaches are neurological conditions that impact quality of life and can require hospitalizations. This study analyzes hospitalizations for these conditions in individuals aged 20 to 59 years in the southeastern region of Brazil from 2019 to 2023, using data from the SIH/SUS of DATASUS. Objective: To analyze the profile of hospitalizations for migraines and other headache syndromes in the southeastern region of Brazil, among individuals aged 20 to 59 years, from 2019 to 2023. Method: This is an ecological, descriptive study with a quantitative approach. It was conducted using data from the Hospital Information System of SUS (SIH/SUS) from DATASUS, focusing on the panel "Migraines and Other Headache Syndromes" (ICD G43 and G44). The variables used were sex, race/color, and age group (20 to 59 years), specifically in the southeastern region of Brazil, from January 2019 to December 2023. Results: During the analyzed period, it was found that hospitalizations of individuals aged 20 to 59 years for migraines and other headache syndromes totaled 33,656 cases. In the southeastern region, 30.18% of this total (N=10,159) were concentrated. Within the southeastern region, the year 2023 had the highest percentage, with 22.63% (N=2,299), and 2021 had the lowest, with 16.39% (N=1,665). There was a predominance among females, white individuals, and those aged 35 to 39 years, accounting for 72.04% (N=7,319), 46.96% (N=4,771), and 14.47% (N=1,470), respectively. Conclusion: Hospitalizations for migraines and headaches in southeastern Brazil show a higher incidence among women, white individuals, and those aged 35 to 39 years. These results highlight the need for targeted health policies for the prevention and proper treatment of these conditions.